Identification of CkSNAP33, a gene encoding synaptosomal-associated protein from Cynanchum komarovii, that enhances Arabidopsis resistance to Verticillium dahliae. - Ping Wang; Xueyan Zhang; Xiaowen Ma; Yun Sun; Nana Liu; Fuguang Li; Yuxia Hou (PLoS ONE, 2017)
SNARE proteins are essential to vesicle trafficking and membrane fusion in eukaryotic cells. In addition, the SNARE-mediated secretory pathway can deliver diverse defense products to infection sites during exocytosis-associated immune responses in plants. In this study, a novel gene (CkSNAP33) encoding a synaptosomal-associated protein was isolated from Cynanchum komarovii and characterized. CkSNAP33 contains Qb- and Qc-SNARE domains in the N- and C-terminal regions, respectively, and shares high sequence identity with AtSNAP33 from Arabidopsis. CkSNAP33 expression was induced by H2O2, salicylic acid (SA), Verticillium dahliae, and wounding. Arabidopsis lines overexpressing CkSNAP33 had longer primary roots and larger seedlings than the wild type (WT). Transgenic Arabidopsis lines showed significantly enhanced resistance to V. dahliae, and displayed reductions in disease index and fungal biomass, and also showed elevated expression of PR1 and PR5. The leaves of transgenic plants infected with V. dahliae showed strong callose deposition and cell death that hindered the penetration and spread of the fungus at the infection site. Taken together, these results suggest that CkSNAP33 is involved in the defense response against V. dahliae and enhanced disease resistance in Arabidopsis.